Prevention of Kidney Disorders Through Fluid and Electrolyte Needs Education in Banyumas, Central Java: Pencegahan Gangguan Ginjal Melalui Edukasi Pemenuhan Kebutuhan Cairan dan Elektrolit pada Ibu-Ibu PKK Kelurahan Kebokura Kecamatan Sumpiuh Kabupaten Banyumas - Nugroho, Irmawan Andri; Septiwi, Cahyu; Waladani, Barkah (Prosiding University Research Colloquium, 2024)
Chronic kidney failure (CKD) is a disease that cannot be transmitted, but it remains a global public health issue. This is a chronic condition with the greatest fatality rate in the world, ranking 20th overall. Being aware of kidney disease risk factors contributes to the early detection and prevention of chronic renal failure. Several risk factors for kidney disease have been identified, including advanced age, a family history of disease, and fluid drinking patterns. PKK moms, a group of persons ranging in age from adults to the elderly, are susceptible to dehydration. Comprehensive education about kidney health and appropriate fluid consumption is required as a promotional and preventive measure. The community service program is implemented. The community service program is carried out by educating activity participants. This activity had 19 participants. Education is carried out through the education, simulations, and discussion. The results of the education revealed an increase in participant knowledge. This was demonstrated by an increase in the average pretest score from 47.5 to 83 at the time of the posttest.